MORPHOFUNCTIONAL CHANGES OF THE THYROID GLAND IN ACUTE EXPERIMENTAL ENDOTOXICOSIS (Multidisciplinary Journal of Science and Technology, 2024)
The aim of the study was to study the morphofunctional changes in the thyroid gland and its hormonal status in rats with non-thyroid diseases caused by acute endotoxicosis. Morphological and morphometric studies of the thyroid gland carried out on the 1st and 7th days of the disease revealed that the earliest sign of non-thyroidal diseases is the separation of synthetic processes and the release of thyroglobulin into the cavity of the follicle and its resorption, that is, the synchronization of the phases of cell secretion, and the thyroid It consists in separating the direction of morphodynamic processes in the central and peripheral zones of the gland.